Twin formation from a twin boundary in Mg during in-situ nanomechanical testing - Jiang, Lin; Kumar, M. Arul; Beyerlein, Irene J.; Wang, Xin; Zhang, Dalong; Wu, Chuandong; Cooper, Chase; Rupert, Timothy J.; Mahajan, Subhash; Lavernia, Enrique J.; Schoenung, Julie M. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2019)
An important fundamental question regarding deformation twinning is whether it is possible for twins to nucleate at boundaries or interfaces when specific stress fields are present. A corollary that follows from this question is: if this is indeed possible, what determines the proper stress field and how does it occur at the nanoscale? Here, we demonstrate the application of an in-situ nanoindentation approach to confine and dynamically capture the stages in the formation of a deformation twin at an internal twin boundary in single crystal Mg. We observe the formation of contraction twin embryos at the pre-existing extension twin boundary, and the subsequent propagation of the twin embryos into the crystal. We reveal an intermediate step, involving the coalescence of tiny embryos into a larger embryo before the nucleus emanates into the crystal. De-twinnning of the twin embryos is captured during unloading and shown to leave a remnant nanosized twin (<10 nm) after complete unloading. A 3D full-field, crystal plasticity model identifies that the twin type and variant selection of the stable embryo are governed by the internal local stress state prevailing at the pre-existing twin boundary. The possible role played by <c+a> dislocations and boundary structure (incoherent vs. coherent) in embryo formation, as suggested by the TEM and modeling analyses, are discussed.